Sarchí: un pueblo con olor a madera - Alfaro, Alicia (2013)
This article presents a journey for the handmade work of the districts of Sarchí Norte and Sarchí Sur of Valverde Vega county. It describes the work of the artisans in each one of the working places and the spaces where wood articles take place. It meditates about the legacy that parents and mothers let to their children in this learning process, and how little by little Sarchí has been characterized as “Cradle of the National Craft”. In this work a series of used terms is clarified, such as craft, carving, and souvenir, among others. Furthermore, it incorporates elements of the handmade culture of Sarchí that emphasize in the tangible and intangible to recover the value that those “workers of the wood” posses in the construction of their own identity, as participants of a popular art rooted in the day to day of a town.